Designing circular innovation ecosystems: insights from stakeholders, values, and investment policies - Asgari, Amir; Asgari, Reza (Frontiers in Sustainability, 2023)
Adopting the circular economy principles as a solution to overcome the challenges of linear economy is increasing globally. In this regard, the related studies showed that circularity is a property of systems, not individual entities. Therefore, any ecosystem design process, including the implementation of circular innovation ecosystems, needs in-depth and comprehensive insights into the design process, transformation of ecosystem components, and transition requirements towards circular ecosystems. The current study utilized a two-step research methodology consisting of a systematic literature review on sustainable innovation ecosystems and circular innovation ecosystems alongside using grounded theory coding procedures to analyze ten interviews based on an analytical ecosystem modeling tool to investigate the transformation of ecosystem components in circular ecosystems. Our findings illustrated that circular ecosystem design needs ecosystem actors' synchronic and incremental evolvement. The results also showed that implementing the circular innovation ecosystems requires the broader networks of stakeholders, a new interactive economic model, an open platform for co-innovation and co-creation, transforming ecosystem value propositions, and defining new investment models and policies. The findings also inform policymakers and ecosystem researchers about the requirements of any transition towards CE ecosystems. Accordingly, proper policy-making structures and models for tackling transformation obstacles are provided.